Altered mRNA Expression of ATP-Sensitive and Inward Rectifier Potassium Channel Subunits in Streptozotocin-Induced Diabetic Rat Heart and Aorta - Yajun Ren; Xianghua Xu; Xiaoliang Wang (Elsevier, 2003)
ABSTRACT: Cardiovascular diseases are the most frequent and costly complication of diabetes. Many previous studies showed that ATP-sensitive potassium channels (KATP) and inward rectifier potassium channels (Kir) play important regulatory roles in functions of cardiovascular tissues. Its still not very clear how these potassium channels are involved in cardiovascular complications of diabetes. We used the streptozotocin (STZ)-induced diabetic rats model to study the expressions of KATP and Kir channel subtypes in diabetic cardiovascular tissues. The mRNA expression levels of Kir2.1, Kir3.1, Kir6.1, Kir6.2, and sulfonylurea receptor (SUR) 2A and 2B subunits in heart and aortal smooth muscles were determined by the reverse-transcription polymerase chain reaction. The results showed that in comparison with the control rats, mRNA expression of SUR 2A was reduced significantly in the diabetic heart (SUR 2A/GAPDH, 1.04 ± 0.16 vs 0.38 ± 0.09, P<0.01, n = 3); SUR 2B was reduced markedly in the aortal smooth muscle of diabetic rats (SUR 2B/GAPDH, 1.13 ± 0.14 vs 0.35 ± 0.07, P<0.01, n = 3). However, there are no significant expression changes of Kir2.1, Kir3.1, Kir6.1, and Kir6.2 in diabetic rats. These results suggested that expression of specific KATP channel subunits were altered in the heart and aorta of diabetic rats.